A versatile semi-empirical PSpice fluorescent lamp model - Yan,W; Tam,E; Hui,SYR (PESC Record IEEE Annual Power Electronics Specialists Conference, 2006)
Based on a recently developed HID lamp model frame, a semi-empirical fluorescent lamp model optimized by genetic algorithms and easily implemented in PSpice is presented. This model does not require any lamp data from lamp manufacturers. Its parameters can be determined from electrical voltage and current measurements of the lamps under ac operation. With the same set of parameters, the model can predict the lamp terminal characteristics accurately under low, medium and high frequency operations. Good simulation results can be achieved when the lamp power is reduced to 60% of rated power and when the lamp is operated under step-up and step-down transient processes. Simulation results for different sizes of tubular and compact fluorescent lamps agree well with their experimental results.